Advances in understanding mineral dust and boundary layer processes over the Sahara from Fennec aircraft observations - Ryder,CL; McQuaid,JB; Flamant,C; Rosenberg,PD; Washington,R; Brindley,HE; Highwood,EJ; Marsham,JH; Parker,DJ; Todd,MC; Banks,JR; Brooke,JK; et al. (Atmospheric Chemistry and Physics, 2015)
The Fennec climate programme aims to improve understanding of the Saharan climate system through a synergy of observations and modelling. We present a description of the Fennec airborne observations during 2011 and 2012 over the remote Sahara (Mauritania and Mali) and the advances in the understanding of mineral dust and boundary layer processes they have provided. Aircraft instrumentation aboard the UK FAAM BAe146 and French SAFIRE (Service des Avions Français Instrumentés pour la Recherche en Environnement) Falcon 20 is described, with specific focus on instrumentation specially developed for and relevant to Saharan meteorology and dust. Flight locations, aims and associated meteorology are described. Examples and applications of aircraft measurements from the Fennec flights are presented, highlighting new scientific results delivered using a synergy of different instruments and aircraft. These include (1) the first airborne measurement of dust particles sizes of up to 300 microns and associated dust fluxes in the Saharan atmospheric boundary layer (SABL), (2) dust uplift from the breakdown of the nocturnal low-level jet before becoming visible in SEVIRI (Spinning Enhanced Visible Infra-Red Imager) satellite imagery, (3) vertical profiles of the unique vertical structure of turbulent fluxes in the SABL, (4) in situ observations of processes in SABL clouds showing dust acting as cloud condensation nuclei (CCN) and ice nuclei (IN) at −15 °C, (5) dual-aircraft observations of the SABL dynamics, thermodynamics and composition in the Saharan heat low region (SHL), (6) airborne observations of a dust storm associated with a cold pool (haboob) issued from deep convection over the Atlas Mountains, (7) the first airborne chemical composition measurements of dust in the SHL region with differing composition, sources (determined using Lagrangian backward trajectory calculations) and absorption properties between 2011 and 2012, (8) coincident ozone and